Patient Recall, Interpretation, and Perspective of an Inconclusive Long QT Syndrome Genetic Test Result. Issue 1 (2nd July 2016) - Predham, Sarah; Hathaway, Julie; Hulait, Gurdip; Arbour, Laura; Lehman, Anna
Abstract: Patients' perceptions of inconclusive results have been previously investigated in cancer genetics. The differences in how patients recall and interpret an uninformative test result compared to a known pathogenic result can affect medical decisions post disclosure. However, there is little to no data available on patients' interpretation and perception of uninformative genetic results in inherited heart disease. We report the results of a qualitative analysis of 16 telephone interviews with participants who received a negative or a variant of unknown significance (VUS) result from Long QT syndrome (LQTS) genetic testing. Our results suggest that the type of result (negative versus VUS) does not affect recall, regardless of the reason for testing. When receiving a negative result, a majority of participants appropriately perceived no change in their diagnosis, while the perception of risk for family members varied. The majority of participants felt they maintained an awareness of their condition after the result disclosure, and that clinical follow‐up was similar to that planned prior to the genetic test result. Further work is needed to determine if there are any differences between obtaining a VUS result versus a negative result in this population.